Impact of Center Point Development Policy Of Indonesia in Coastal Communities In Makassar City, South Sulawesi - Guntur, Muhammad; Siraj, Muhammad Luthfi (Jurnal Office, 2023)
The government is carrying out physical development, namely the construction of the Centra Point of Indonesia (CPI) which is being built in the Tanjung Bunga beach area, Makassar Bay, namely the construction of business and government centers, holiday areas, world-class hotels with a total area of 157 hectares. This research aims to determine the impact of policies and changes in space utilization for the Mega Project (CPI) development on the economy of coastal communities in Community City. The type of research is qualitative through interviews and field observations to explore the required data from sources related to the impact of development policies (CPI) in improving the economy of communities around development (CPI). The results of this research show that most of the people living on the coast have experienced a change in their job status from fishermen as fish finders to entrepreneurs, both in trade and service businesses. Changes in the employment status of fishermen actually have an impact on improving the economy of coastal communities. The positive impact of the development policy (CPI) is the change of land on the coast of Makassar City into a residential area, business area, the creation of road access connecting Makassar City with Takalar and Gowa Regencies. This research can be used as a reference for future researchers regarding the impact of Center Point of Indonesia development policies using qualitative research methods.